Association between N-terminal pro-brain natriuretic peptide levels and outcomes of ischemic stroke: A systematic review and meta-analysis - Yehong Zhang; Jingjia Zheng; Fangyong Xu (PLoS ONE, 2025)
Background N-terminal pro-brain natriuretic peptide (NT-proBNP) was identified as an important biomarker of cardiovascular disease, in ischemic stroke. This study intends to assess the association of NT-proBNP levels with clinical outcomes of patients ischemic stroke patients. Methods A comprehensive search of MEDLINE, Web of Science, ScienceDirect, and Cochrane CENTRAL electronic databases was done for papers published till April 2024 and reporting on the levels of NT-proBNP in patients with ischemic stroke. Outcomes of interest included mortality (all-cause and cardiovascular) and neurological, and functional outcomes. A random-effects meta-analysis model was used, and final estimates were reported as pooled odds ratio (OR) with 95% confidence interval (CI). Results Elevated NT-proBNP levels were significantly linked to increased all-cause (pooled OR = 2.322, 95% CI: 1.718 to 2.925) and cardiovascular mortality (pooled OR = 1.797, 95% CI: 1.161 to 2.433). Higher NT-proBNP levels were also related to poorer functional outcomes (pooled OR = 1.129, 95% CI: 1.041 to 1.217). Patients with higher NT-proBNP levels had somewhat worse neurological outcomes (pooled OR = 1.317, 95% CI: 0.859 to 1.774). Considerable heterogeneity was detected across the studies (I² > 40% in most analyses). Conclusion NT-proBNP levels may serve as a robust predictor of mortality and offer potential utility in predicting functional recovery in ischemic stroke patients. The integration of NT-proBNP measurement into clinical settings may be beneficial for risk stratification and management of stroke survivors.